Superimposed Folding of the Precambrian Metamorphic Rocks of the Lutzow-Holm Bay Region, East Antarctica (Earth Sciences) - ISHIKAWA, Terumi (1976)
P(論文) The Lutzow-Holm Bay region (latitude 69°S longitude 38°E to 40°E) is located in the Prince Olav Coast of Enderby Land of East Antarctica, where crystalline basement rocks extensively occur under the glacial cover. These basement metamorphic rocks in the Ongul Islands, Langhovde, Breidvagnipa, Skarvsnes, Kjuka and Skallen areas, entirely of Precambrian age, are geologically investigated, and the geologic maps of these areas are presented. In the metamorphic rocks of the Lutzow-Holm Bay region are recognized many phases of deformation during late Precambrian to Paleozoic time three major folding events, designated as F_1, F_2, F_3, and fracturing after F_3 are clearly recorded in them. The first folding event, F_1, under the granulite facies metamorphism is characterized by an isoclinal recumbent fold with N-S axial trace. The second folding event, F_2, occurred under the amphibolite facies metamorphism, showing a concentric fold with E-W axial trace. The third event denoted as F_3 took place under a metamorphic condition lower than the amphibolite facies, forming a concentric fold with N-S axial trace. Fracturing associated with an upheaval of the basement after the last phase of folding occurred over the whole region. Discussion is extended to the geological history of this region and the Ross orogeny that had been widespread in the East Antarctic shield. departmental bulletin paper